Collecting wild potato species (Solanum sect. Petota) in Peru to enhance genetic representation and fill gaps in ex situ collections - Sotomayor, Diego A.; Ellis, David; Salas, Alberto; Gomez, Rene; Sanchez, Rosa A.; Carrillo, Fredesvinda; Giron, Carolina; Quispe, Violeta; Manrique-Carpintero, Norma C.; Anglin, Noelle L.; Zorrilla, Cinthya (Frontiers in Plant Science, 2023)
Crop wild relatives (CWRs) are important sources of novel genes, due to their high variability of response to biotic and abiotic stresses, which can be invaluable for crop genetic improvement programs. Recent studies have shown that CWRs are threatened by several factors, including changes in land-use and climate change. A large proportion of CWRs are underrepresented in genebanks, making it necessary to take action to ensure their long-term ex situ conservation. With this aim, 18 targeted collecting trips were conducted during 2017/2018 in the center of origin of potato (Solanum tuberosum L.), targeting 17 diverse ecological regions of Peru. This was the first comprehensive wild potato collection in Peru in at least 20 years and encompassed most of the unique habitats of potato CWRs in the country. A total of 322 wild potato accessions were collected as seed, tubers, and whole plants for ex situ storage and conservation. They belonged to 36 wild potato species including one accession of S. ayacuchense that was not conserved previously in any genebank. Most accessions required regeneration in the greenhouse prior to long-term conservation as seed. The collected accessions help reduce genetic gaps in ex situ conserved germplasm and will allow further research questions on potato genetic improvement and conservation strategies to be addressed. These potato CWRs are available by request for research, training, and breeding purposes under the terms of the International Treaty for Plant Genetic Resources for Food and Agriculture (ITPGRFA) from the Instituto Nacional de Innovacion Agraria (INIA) and the International Potato Center (CIP) in Lima-Peru.